Techno-economic aspects of the glass industry in the West African Sub-region (Niamey : Economic Commission for Africa, 1966)
Economic Commission for Africa Sub-regional meeting on Economic Co-operation in West Africa held in Niamey, Niger on Techno-Economic aspects of the glass industry in the West-African Sub-region.
rpm 14/02/2019
Loans
Keywords: Industrialization; Glass Industry; West Africa